High-Performance Thin-Layer Chromatographic Quantification of Rosmarinic Acid and Rutin in Abnormal Savda Munziq - S. G. Tian; L. D. Xin; Halmuart Upur (Journal of Chemistry)
A high-performance thin-layer chromatographic (HPTLC) method has been established for simultaneous analysis of rosmarinic acid and rutin in Abnormal Savda Munziq (ASMq). A methanol extract of ASMq was used for quantification. The compounds were separated on silica gel H thin layer plate with ethyl acetate-formic acid-acetic acid-water 15 : 1 : 1 : 1.5 (v/v) as a developer, trichloroethanol as the color reagent. The plates were scanned at 365 nm. The linear calibration data of rosmarinic acid and rutin were in the range of 0.0508 to 0.2540 μg (r=0.9964), 0.2707 to 1.35354 μg (r=0.9981), respectively. The recovery rate of rosmarinic acid was 99.17% (RSD = 2.92%) and rutin was 95.24% (RSD = 2.38%). The method enables rapid screening, precise, selective, and sensitive quantification for pharmaceutical analysis.